Late Quaternary Sea Level Changes on Brock and Prince Patrick Islands, Western Canadian Arctic Archipelago - Hodgson, Douglas; Taylor, Robert; Fyles, John (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1994)
ABSTRACTEmerged shorelines are few and poorly defined on Prince Patrick and Brock islands. The sparse radiocarbon dates show emergence of only 10 m through the Holocene on the Arctic Ocean coast, increasing to 20 m 100 km to the east. Hence, from Brock Island, representative of westernmost coasts, the sea level curve since the latest Pleistocene has a very low gradient, whereas on eastern Prince Patrick Island the curve takes the more typical exponential form. A decline in isobases towards the west is thus registered. Drowned estuaries, breached lakes, and coastal barriers, particularly in southwest Prince Patrick Island, suggest that the sea is now transgressing at a rate that decreases towards the north end of the island, hence there is also a component of tilt to the south. Delevelling is assumed to result from undefined ice loads, but may have a tectonic component. The sole prominent raised marine deposit is a ridge probably built in a period of more mobile sea ice, possibly at a time of stable or slightly rising sea level in the middle or early Holocene. It winds discontinuously along several hundred of kilometres of the shores of the Arctic Ocean and connecting channels, declining to the south.